Cultural Crisis and Danny Reveco: On the Cultural Politics of Crime and Street Art in Chile. - Woods, Maxwell (Bulletin of Latin American Research, 2026)
In December 2023, the Valparaíso‐based artist, Danny Reveco, opened his exhibition, 'Language Is Not Sufficient'. A month later, it was the catalyst of a cultural crisis when it was argued that Reveco's works were criminal acts. I recommend that Reveco was principally concerned with how the Chilean State interpellates residents in the national territory according to the 'good behaviour' of a proper citizen. Those who do not fulfil that good behaviour are deemed criminals. On the other hand, those cultural authorities who labelled the exhibition as criminal were trying to win a renewed legitimacy for the Chilean State.